2018
DOI: 10.1111/vop.12587
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bacteria and fungi sampled from the conjunctival surface of normal horses in South‐East Queensland, Australia

Abstract: Bacteria and fungi were commonly isolated from the eyes of healthy horses. The antibiotic and antifungal susceptibilities identified can be used as a guide for empirical therapy after cytology in the treatment of corneal ulceration in horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 17 publications
5
27
0
8
Order By: Relevance
“…The most frequently isolated bacteria were gram-positive (Table 1), which is consistent with other studies 14,[23][24][25] but in contrast to Johns et al who found the gram-negative rod Acinetobacter to predominate in conjunctival samples from healthy horse eyes in the South East of the UK. 20 It is also in contrast to a study from Florida, USA, where Pseudomonas aeruginosa and Streptococcus spp.…”
Section: Discussionsupporting
confidence: 90%
“…The most frequently isolated bacteria were gram-positive (Table 1), which is consistent with other studies 14,[23][24][25] but in contrast to Johns et al who found the gram-negative rod Acinetobacter to predominate in conjunctival samples from healthy horse eyes in the South East of the UK. 20 It is also in contrast to a study from Florida, USA, where Pseudomonas aeruginosa and Streptococcus spp.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, the ocular surface is not abundantly colonized by bacteria, with frequent reports of no growth from samples of healthy horse eyes [2, 9–12]. This finding highlights the limitations of culture-based methods, as many bacterial organisms do not grow well in laboratory conditions and thus cannot be readily identified in a given sample.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, bacterial microorganisms on the ocular surface of both healthy and diseased horses have been studied using conventional culture-based techniques [1–4,812]. Gram-positive bacteria were reported to predominate the equine ocular surface, with Bacillus , Staphylococcus , Streptococcus , and Corynebacterium spp .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations